Spatio-Temporal Detection of Accessibility Change on Health Care: A Case Study for Istanbul - Shoman, Wasim; Demirel, Hande (Aperta, 2019)
Reaching health centers and hospitals in shorter traveling time is definitive for citizens. To assure that, cities heavily invest in enlargement and development of transportation infrastructure especially by constructing new links. The performance of such investments could be measured via spatial accessibility indices that quantifies the ease of reaching destinations. The most prominent accessibility indices are potential and daily accessibility that take into account development of urban networks and changes in land cover/use.